The General Structure of The Dark Personality of University Students - khaled Rafeek Badawy (International Journal of Instructional Technology and Educational Studies)
The study aimed to identify the factor structure of the dark personality of university students. The sample consisted of (500) male and female students from the fourth year of university students, their ages ranged between (21 - 22) years with an average of (20.24) years and a standard deviation of (2.80). The researcher used the tools of the Life Orientation Scale of Johnson and Paul (2014). The results showed that: There is one general factor that links the three dimensions of the dark personality of university students, and there is no correlation between Machiavellianism and psychopathy among university students. There is also a positive correlation between narcissism and both Machiavellianism and psychopathy among university students, which indicates that the narcissism factor links the three dimensions of the personality of university students. The results also indicated that there is no statistically significant effect of the gender variable on the dependent variable for the personality (Machiavellianism - psychopathy), and there is a statistically significant effect The gender variable on the dependent variable (three-dimensional personality) for the personality (narcissism) in favor of females, the absence of a statistically significant effect for the specialization variable (literary - scientific) on the dependent variable (psychopathy), the presence of a statistically significant effect for the specialization variable (literary - scientific) on the dependent variable (Machiavellianism, narcissism) in favor of the scientific, and the results did not reveal an effect of the interaction between the independent variables (gender, specialization) on the three-dimensional personality among university students